Improving small system transportation a focus on Fond Du Lac area transit - Kunde, Joey (My University, 2018)
Public Transportation can mean many different things; it all depends on the person you ask. It could mean a way to school, work, doctors’ appointments, or lunch. However, to others it is a waste of federal, state, and local funds. Cities and towns with small, urbanized bus systems seem to face these negative issues due to ample parking and low traffic congestion. So, then why do small cities continue to support the small urbanized bus system? Lee, Wohar, and Uhm (2016) states, “Bus services in small…urban areas provide increased mobility to individuals who have no other means of transportation (p.861).” In general, it is to help the people who have no other option, such as the elderly or poor. Public transportation can specifically help those who could not get work because they cannot afford a car, or for the handicapped or elderly who cannot drive. Fond du Lac Area Transit is one such system. Fond du Lac Area Transit (FDLAT) is the smallest urbanized transit system in the United States, and is easily overlooked by the general public. FDLAT is located in Fond du Lac, Wisconsin, a city with a population around 50,000. It has a small transportation system that has increased ridership by 9.8% from 2011 to 2015 according to the Legislative Fiscal Bureau 2017 paper on Mass Transit Funding (Horton, 2017, p.3). It presently operates five weekday bus routes and one school tripper route with complimentary paratransit services (Handi-van and Non-ADA) and taxi service where buses do not operate. I am seeking to improve the performance of and provide answers to some of the issues FDLAT and other small transportation systems face. These issues are decentralization, cost, socioeconomic issues, and lack of education. Research and data collection are important in order to provide better transportation for all.
A field project submitted in partial fulfillment of the requirements for the degree of Master of Public Administration
Keywords: Rural transportation; Transportation